Prevalence and Socioeconomic Status Correlation of Depressive Symptoms among Children Living in Urban Beijing - Shang, MPH, Xianwen; Wang, MD, Msc, Dong; Wang, PhD, Jianping; Hu, MD, Xiaoqi; Du, PhD, Songming; Li, PhD, Yanping (North American Journal of Medicine and Science, 2010)
Background: The prevalence of depressive symptoms among children is rapidly increasing all over the world. The objective of this study was to investigate the prevalence of depressive symptoms and its socioeconomic characteristics among children living in urban Beijing of China. Results: The prevalence of depressive symptoms in children aged 7-12 years was 11.6%, which included 14.7% among boys and 8.3% among girls. The children aged 11-12 years had a significantly higher prevalence of depressive symptoms (18.7%) as compared to the younger ones. The likelihood of depressive symptoms in children tended to increase significantly with the decreasing in their father’s education level, mother’s education level, and family income level. A significantly higher likelihood of depressive symptoms was also observed among children whose parents were farmers, unemployed, self-employed, or those whose fathers were waiters and/or whose mothers were soldiers or policewomen. Conclusions: Depressive symptoms are common in children living in urban Beijing, especially among children in families with low socioeconomic status.